BO‘LAJAK TARBIYAChILARNING KOGNITIV QOBILIYATLARINI RIVOJLANTIRISh METODIKASINI TAKOMILLAShTIRIShNING DIDAKTIK TA’MINOTI - Bazarbaeva, A.K. (SCIENCE and SOCIETY, 2025)
In the article, it proves the cognitive abilities of future educators include the educator’s attitude towards learning, the ability to receive and process given information, creative and critical thinking. This is of great importance for the development of their abilities, improving the qualifications of future educators, and their effective work in organizations.